Molecular and Histological Changes in Airway Basal Stem Cells on Chronic Obstructive Pulmonary Disease - Dewi, A. A. Ayu Asri Prima; Inayati, Rizqa; Sumadewi, Komang Trisna; Kerans, Fransiscus Fiano Anthony (International Journal Labs, 2023)
Airway basal stem cell changes in COPD including hyperplasia, squamous cell metaplasia, epithel-mesenchymal transision, impairment of cillia and secretoric non mucosal cell differentiation, and junctional barrier integrity disturbances that lead to histological changes. There are also molecular changes such as disturbances in gene expresion, cytokines, inflamation factor and dysregulation of basal cell transcriptome in locus 19q13.2. This article is aimed to review airway basal cell changes in COPD. By understanding initial changes of airway basal stem cell in COPD, hopefully can help to develop stem cell therapy in COPD treatment. The research aims to explore molecular and histological changes in airway basal stem cells on chronic obstructive pulmonary disease. The researchers used literature review as the way to verify their arguments on the issue discussed by analyzing the results of scientific sources, especially from trusted sources such as Google Scholar and Science Direct. The study continues by stating that regenerative therapy using stem cells has started to evolve with the advancement of stem cell technology and is anticipated to improve and treat this illness. Only preclinical and phase 2 clinical trials have seen recent advancements in the use of stem cells for treating COPD.